Gulf Crisis: Rewriting the Political Map? - Dorsey, James Michael (2017)
A rupture in Arab diplomatic and economic relations with Qatar as well as the Gulf state’s involvement with a Saudi-led, 41-nation Sunni Muslim military alliance threatens to force non-Arab Muslim nations as well as China to choose sides.